1983
DOI: 10.2105/ajph.73.5.573
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of public health nurse home visits to primarous mothers and their infants.

Abstract: The purpose of this study was to determine the effects of public health nurse postpartum home visits by comparing the health outcomes of 67 randomly selected mother-infant pairs who had received such services with 43 randomly selected mother-infant pairs who had not received them. Health outcome variables were mother's health and health services utilization, infant's health and health services utilization, and mother's parenting practices. Data

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 13 publications
1
41
0
Order By: Relevance
“…Forchuk (1992) and Forchuk and Brown (1989) observed that nurse–client relationships develop at various rates and that several encounters are often needed before problem solving begins. This would partially explain why evaluations of client outcomes after one or two nursing encounters are often disappointing (for example, Barkauskas, 1983; Oda et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Forchuk (1992) and Forchuk and Brown (1989) observed that nurse–client relationships develop at various rates and that several encounters are often needed before problem solving begins. This would partially explain why evaluations of client outcomes after one or two nursing encounters are often disappointing (for example, Barkauskas, 1983; Oda et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The most promising impact of two or less nursing encounters has been its influence on client's use of other health care services (Bradley & Martin, 1994; Ghilarducci & McCool, 1993; Oda & Boyd, 1988; Zotti & Zahner, 1995). Other researchers have found no significant difference in health outcomes between control groups and clients who received one or two nursing contacts (Barkauskas, 1983; Oda, Heilbron, & Taylor, 1995; Stanwick, Moffat, Robitalle, Edmond, & Dok, 1982). Byrd (1997) described the customary single postpartum home visit as primarily a screening activity in which the PHN provides as much health and referral information as possible.…”
Section: Literature Reviewmentioning
confidence: 96%
See 1 more Smart Citation
“…However, the results have been less consistent for premature infants, and several studies have failed to document improved outcomes for premature infants from mixed racial-ethnic populations with multiple social-environmental risks (Barkauskas, 1983; Bryant & Maxwell, 1997; Siegel, Bauman, Schaefer, Saunders, & Ingram, 1980; Zahr, 2000). The largest intervention for premature infants, the Infant Health and Development Project, begun 20 years ago, included both early home visits and developmentally based center care through age 3.…”
Section: Calloutmentioning
confidence: 99%
“…Researchers have also been attempting to identify public health nursing (PHN) roles (Gulino & LaMonica, 1986), examine results of interventions (Combs-Orme, Reis, & Ward, 1985;Barkauskas, 1983), and determine costs of services (Oda, Fine, & Heilbron, 1986).…”
mentioning
confidence: 99%